A CRITICAL LEGAL STUDIES PARADIGM OF THE PRESIDENTIAL THRESHOLD ELECTORAL SYSTEM IN INDONESIA: PARADIGMA CRITICAL LEGAL STUDIES TENTANG SISTEM PEMILU PRESIDENTIAL THRESHOLD DI INDONESIA - Kurniawan, Anfal (Constitutional Law Society, 2024)
In the perspective of the Critical Legal Studies Paradigm, researchers do not have the intention to deliberately dismantle normative legal rules that are legally and constitutionally, but in this discourse the critical legal studies paradigm provides a lens that critical voices are voices that come from the people with a higher realm of awareness in view with the assumption of potential that will occur critically, involving the direction of thinking that tends to be deconstructive and very worthy of questioning. in this case the paradox that occurs between ontology and methodology or in simple language reality with normative methodological values itself, by separating political, sociological, historical, and ethical motives. In this case, the paradox that occurs between ontology and methodology or in simple language reality with normative methodological value itself, by separating political, sociological, historical, and ethical motives. in this study, researchers used a qualitative method based on the study of the normative rules of the 1945 Constitution. normatively in article 222 of Law Number 17 of 2017 concerning the election of the President and Vice President reads: The candidate pair is proposed by a political party or a coalition of political parties participating in the election that meets the requirements of obtaining at least 20% (twenty per cent) of the total seats in the DPR or obtaining 25% (twenty five per cent) of the national valid votes in the election of DPR members, before the implementation of the Presidential and Vice Presidential elections or the Presidential Threshold system if viewed deconstructively from the process of forming the rules of the Law or the legislature itself does not have a basic limiting framework of legal construction, With the pretext of strengthening the presidential system, the effectiveness of holding elections in an accountable manner, but ontologically or in reality this raises that the law is a political product is a reality and shows that political power is more dominant than the law itself, of course this is very paradoxical with the concept of a country that is considered democratic where political power should be subject to the law. In this foundation, something produced by the legal products of the legislature is worthy of criticism.